Editorial Note - k, mandalp (Journal of Meat Science, 2022)
It is a matter of pride and an honour for Indian Meat Science Association (IMSA) to regularly  publish the only journal in the field of meat science and technology in India to advance the  knowledge and to disseminate the recent developments among researchers, faculty members,  regulatory agencies, students and meat Industry personnel. We feel happy to print this 13th  volume and second issue of 2018 in which for the first time we have included one “policy brief”  along with 11 research papers in different areas of meat quality, processing, value addition, safety  and sensory attributes.  We are glad to mention that, the current issue of the JMS including submission of papers,  reviewing, incorporating corrections, resubmission and acceptance was completely handled  online. We are now working towards inclusion of JMS under UGC-Consortium for Academic  Research and Ethics (UGC-CARE) list to ensure high quality of papers and provide better  solutions to authors.  We urge all the scientists, faculty and students from different Universities to undertake  state-of the art, cutting edge basic and applied research in the relevant areas of meat science and  technology, to do thorough literature search, statistical analysis, compilation and strive to submit  quality research papers. With emerging challenges related to meat sector viz, green-house gas  emission, animal welfare, water usage and environmental impact, antimicrobial resistance, safety  issues in meat, halal authentication etc. and research efforts need to be diverted towards finding  solutions to such problems.  We are sure, everyone will get plenty of opportunities to discuss several of these topics  in the forthcoming IX-IMSACON and International Symposium on “Advances in production,  processing and quality assurance of muscle foods for improved health and nutritional security”  to be held at DGCN College of Veterinary and Animal Sciences, CSK HPKV, Palampur, HP  from 6-8th November, 2019. All the Executive Committee members and Editorial Board of JMS  welcomes IMSA members to participate and make the 9th IMSACON a grand success.
Keywords: (UGC-CARE); IX-IMSACON; DGCN; IMSA; CSK HPKV